Adapting to climate change: responses of fine root traits and C exudation in five tree species with different light-use strategy - Sell, Marili; Rohula-Okunev, Gristin; Kupper, Priit; Ostonen, Ivika (Frontiers in Plant Science, 2024)
Trees that are categorised by their light requirements have similarities in their growth strategies and adaptation mechanisms. We aimed to understand the complex responses of elevated air humidity on whole tree fine root carbon (C) exudation (ExC) and respiration rate, morphology, and functional distribution in species with different light requirements. Three light-demanding (LD) species, Populus × wettsteinii, Betula pendula, and Pinus sylvestris, and two shade-tolerant species, Picea abies and Tilia cordata saplings were grown in growth chambers under moderate and elevated air relative humidity (eRH) at two different inorganic nitrogen sources with constant air temperature and light availability. The proportion of assimilated carbon released by ExC and respiration decreased at eRH; up to about 3 and 27 %, respectively. There was an indication of a trade-off between fine root released C and biomass allocation. The elevated air humidity changed the tree biomass allocation and fine root morphology, and the responses were species-specific. The specific fine root area and absorptive root proportion were positively related to canopy net photosynthesis and leaf nitrogen concentration across tree species. The variation in ExC was explained by the trees' light-use strategy (p < 0.05), showing higher exudation rates in LD species. The LD species had a higher proportion of pioneer root tips, which related to the enhanced ExC. Our findings highlight the significant role of fine root functional distribution and morphological adaptation in determining rhizosphere C fluxes in changing environmental conditions such as the predicted increase of air humidity in higher latitudes.